It's not just numbers: Cultural identities influence how nutrition information influences the valuation of foods. Issue 3 (16th January 2015) - Gomez, Pierrick; Torelli, Carlos J.
Abstract: This research examines how cultural mindsets cued by a salient identity can influence how consumers interpret seemingly benign nutrition information in foods. Results show that nutrition information can be incongruent with the cultural norm of food enjoyment distinctively associated with French (and not American) identity. This occurs because of a conflict between the motivation to enjoy foods activated by a salient French identity and the utilitarian nature of nutrition information in foods – that does not belong to a French‐culture mindset. Three studies demonstrate that French (and not American) consumers with a salient cultural identity are more sensitive (i.e., perceive as riskier for their health) and evaluate more negatively foods that display (vs. not) nutrition information. Furthermore, this devaluation effect is mediated by anticipated feelings that the foods would not be enjoyable. Providing further evidence for the motivational inconsistency between the culturally‐distinctive norm of food enjoyment cued by a salient French‐culture mindset, French (and not American) consumers with a salient (vs. not) cultural identity experienced more disfluency when processing nutrition information in foods.